A case of CDKL5 deficiency disorder with a novel intragenic multi-exonic duplication - Takato Akiba; Shino Shimada; Katsumi Imai; Satoru Takahashi (Human Genome Variation)
Abstract We present a case of suspected CDKL5 deficiency disorder (CDD) in which a novel intragenic multi-exonic duplication in the CDKL5 gene was identified using next-generation sequencing and multiple ligation-dependent probe amplification. This duplication was assumed to result in a shift of the reading frame and the introduction of a premature stop codon. This case highlights the importance of careful phenotyping and comprehensive genetic testing to detect rare structural variants in CDD patients.